Checkpoint Maths workbook 2 - "Pimentel, Ric" (London; Hodder Education, 2012)
Consolidate learning with a write-in book for use in class and for homework with a parallel practice exercise for every exercise in the Student's Book.
Keywords: Mathematics-Textbook